GAMBARAN PERILAKU KELUARGA DALAM MANAJEMEN HALUSINASI PADA ANGGOTA KELUARGA DENGAN SKIZOFRENIA DI WILAYAH KERJA PUSKESMAS IMOGIRI II - Densa Anggiviani Prity; Tri Prabowo; Sarka Ade Susana (Caring : Jurnal Keperawatan, 2017)
Schizophrenia is a disorder that occurs in the human brain that causes a very dramatic behavior change. Positive symptoms of schizophrenia are hallucinations. Based on a report from Imogiri II Public Health Center in 2016 there were 218 people with mental disorders in which 70% experienced hallucinations. Family is the closest person and has an active role in providing direct care to people with schizophrenia. The purpose of this study is to know the description of family behavior in hallucination management in family members with schizophrenia in the working area of ??Imogiri II Community Health Center. This research uses descriptive research type as a research design. The sampling technique used is simple random sampling with 78 respondents. The research instrument used is a questionnaire. The result of the research showed that 78 respondents in the range of age 41-60 years old (51.28%), the last educated is elementary (46.15%), most of the respondent is jobless (51.28%), respondent is parent of schizophrenia family (29.49%), and had take care for more than of 10 years (33.33%), respondents knowledge level mostly good (57.69%) and respondent attitude mostly positive (58.97% ). The description of behavior in hallucination management in family members with schizophrenia is in good category (57.69%). The results of this study recommend the need for motivation and support from health services to maintain good family behavior in hallucination management so that there is no risk of violent behavior and recurrence in schizophrenic patients with hallucinations.